Multiple Electronic and Structural Factors Control Cyclobutane Pyrimidine Dimer and 6–4 Thymine–Thymine Photodimerization in a DNA Duplex. Issue 60 (9th October 2017) - Conti, Irene; Martínez‐Fernández, Lara; Esposito, Luciana; Hofinger, Siegfried; Nenov, Artur; Garavelli, Marco; Improta, Roberto
Abstract: The T–T photodimerization paths leading to the formation of cyclobutane pyrimidine dimer (CPD) and 6–4 pyrimidine pyrimidone (64‐PP), the two main DNA photolesions, have been resolved for a T–T step in a DNA duplex by two complementary state‐of‐the‐art quantum mechanical approaches: QM(CASPT2//CASSCF)/MM and TD‐DFT/PCM. Based on the analysis of several different representative structures, we define a new‐ensemble of cooperating geometrical and electronic factors (besides the distance between the reacting bonds) ruling T–T photodimerization in DNA. CPD is formed by a barrierless path on an exciton state delocalized over the two bases. Large interbase stacking and shift values, together with a small pseudorotation phase angle for T at the 3′‐end, favor this reaction. The oxetane intermediate, leading to a 64‐PP adduct, is formed on a singlet T→T charge‐transfer state and is favored by a large interbase angle and slide values. A small energy barrier (<0.3 eV) is associated to this path, likely contributing to the smaller quantum yield observed for this process. Eventually, a clear directionality is always shown by the electronic excitation characterizing the singlet photoactive state driving the photodimerization process: an exciton that is more localized on T 3 and a 5′‐T→3′‐T charge transfer for CPD and oxetane formation, respectively, thus calling for specific electronic constraints. Abstract : CASPT2//CASSCF/MM and TD‐DFT/PCM calculations disentangle the complex structural–electronic–electrostatic factors driving Thy–Thy cyclobutane pyrimidine dimer (CPD) and 6–4‐photoinduced formation in a DNA duplex (see figure).